Prevalence of pregnancy induced hypertension and associated factors in Kashmiri women attending a tertiary care hospital at Srinagar: a cross-sectional study - Ain, Syed Najmul; Gull, Shayista; Qulsum, Reyana; Khan, Zahid Ali; Qureshi, Uruj Altaf (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Pregnancy induced hypertension (PIH) is a significant cause of morbidity among pregnant females and also affects the foetal outcome. Numerous risk factors have been identified. This study was conducted to estimate the prevalence of PIH and the factors associated with PIH. Methods: This was a cross-sectional hospital-based study. Pregnant women admitted for delivery in the gynaecology and obstetrics department of SKIMS Soura formed the study participants. Patients with chronic hypertension were excluded. A minimum sample size of 295 was calculated but finally a sample of 402 was achieved. The data was collected over a 3-month period from July to September 2021 using convenient sampling. Data was entered in Microsoft excel and analysed using IBM SPSS version 23. Results: A total of 402 pregnant women were included. Majority (61%) of the participants were up to 30 years of age, majority (97.8%) were up to para 3 and 89% were literate. The prevalence of PIH was 6.5%. Hypertension was more frequent among the women with age more than 30 years (p=0.041) and women with higher pre-pregnancy BMI (p=0.010). Maternal education, occupation and parity were not associated with hypertension in pregnancy. Conclusions: In our study older women and women with higher body mass index (BMI) were more at risk of having PIH in pregnancy. Therefore, we would recommend earlier age at marriage and lifestyle modification for maintaining normal BMI.